Students’ satisfaction with simulated skills in simulation labs unit - Rateb Abuzeid; Samer Al Haliq; Abdalmajeed Mobrad; Nabeel AbdulQader; Ahed Al Najjar; Romeo Bangasan (Institute of Advanced Engineering and Science, 2022)
Examining students’ contentment with simulation is crucial for giving local and foreign academic teaching personnel feedback. The purpose of this study was to compare students studying emergency medical services’ simulation satisfaction. There were 193 students involved in a comparison cross-sectional design during the second semester of the academic year 2018 utilizing a paper-based English version of the satisfaction with simulation experience scale. The findings revealed a slight to moderate positive correlation for factor two (clinical reasoning), 0.510 (P<0.001); and factor three (clinical learning), 0.628 (P<0.001) for students. A slight negative correlation was also found in factor one (debrief and feedback) 0.092 (P<0.001). The study showed that the reliability was 0.906 for factor one, 0.860 for factor two and 0.872 for factor three. Cronbach’s Alpha for all factors: 0.937. ANOVA showed that factor three is significant with students’ level (df 3, f, 4.186, sig. 0.007). Compared to other factors, students were less satisfied with clinical learning simulation, due to unfamiliarity of students with the simulation mannequin and environment. The frequent implementation of simulation practice in emergency medical services field is highly recommended to enhance mainly clinical learning, master new skills and satisfaction with the learning experience.